How does education affect the earnings distribution in urban China? - Le Wang (Institute for the Study of Labor (IZA), 2011)
China's phenomenal growth is accompanied by both relatively low level of standards of living and high inequality. It is widely believe that investing in education could be an effective strategy to promote higher standards of living as well as to reduce inequality. However, little is known about whether this belief is empirically supported. To this end, we employ a recently developed distributional approach to estimate returns to education across the whole earnings distribution in urban China during economic transition. We find that returns to education are generally more pronounced for individuals in the lower tail of the earnings distribution than for those in the upper tail, in stark contrast to the results found in developed countries. Our result implies that education indeed reduces earnings inequality while increasing individuals' earnings. We also find that the returns to education are uniformly larger for women than for men across the distribution. The results suggest the presence of added effects of education on earnings, as opposed to productivity-enhancing effects, for disadvantaged groups. Finally, we find that rates of educational return increased over time for all parts of the earnings distribution.
urn:nbn:de:101:1-201201103042
Keywords: J24; J61; J31; J7; J15; C31; 330; returns to education; inequality; gender gap; economic transition; instrumental variable quantile regression